2009
DOI: 10.1007/s10750-009-9753-5
|View full text |Cite
|
Sign up to set email alerts
|

Biology of the freshwater diatom Didymosphenia: a review

Abstract: Features of the colonial diatom Didymosphenia are reviewed, especially D. geminata. Although there is a long record of its occurrence in north temperate regions, mass growths have been reported much more widely in recent years. Contrary to some statements in the literature, there are also reliable older records for the southern hemisphere, though the first report of mass growth was in New Zealand in 2004. The annual cycle of morphological changes in D. geminata in northern England, and probably elsewhere, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
1
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 95 publications
10
106
1
6
Order By: Relevance
“…An extreme example of an organism whose competitive success almost certainly depends on the presence of organic phosphate is the diatom Didymosphenia geminata (Whitton et al, 2009). Rivers and streams with Didymophenia often drain catchments with peaty soils overlying base-rich rocks, such as the one in the R. Swale catchment where FHP formed on average 85% TFP (Ellwood et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…An extreme example of an organism whose competitive success almost certainly depends on the presence of organic phosphate is the diatom Didymosphenia geminata (Whitton et al, 2009). Rivers and streams with Didymophenia often drain catchments with peaty soils overlying base-rich rocks, such as the one in the R. Swale catchment where FHP formed on average 85% TFP (Ellwood et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Some internal differentiation was observed in the stalks (Fig. 6), and a distinct tubular structure was observed, such as occurs in the middle of the stalks of the colonial diatom Didymosphenia (Ellwood & Whitton, 2007;Whitton et al, 2009;Aboal et al, 2012), where it has been suggested it may aid rapid transfer of phosphate to the cell, such as might occur with a gradient resulting from rapid P uptake by the cell.…”
Section: Río Chícamomentioning
confidence: 99%
“…Recent research has focused primarily on the biology and distribution of D. geminata (Kawecka and Sanecki 2003, Kilroy et al 2005, Kilroy et al 2006, Kirkwood et al 2007, Spaulding and Elwell 2007, Whitton et al 2009). Other recent research on invertebrate communities has shown that invertebrate composition tends to shift from larger taxa (i.e., Ephemeroptera, Plecoptera, Trichoptera) to smaller taxa such as Diptera in areas impacted by D. geminata (Shelby 2006, Shearer et al 2007, Larson and Carreiro 2008, Gillis and Chalifour 2009, Kilroy et al 2009).…”
Section: Introductionmentioning
confidence: 99%